Saúde mental no contexto escolar: as percepções dos professores que atuam em escolas públicas de Bragança, Pará - ROCHA, Karina Raquel Galvão da (2024)
This study investigated the perceptions of teachers about the psychological suffering experienced by students in the school context. Methods: This descriptive and exploratory study, with a qualitative approach, was developed with teachers working in the final years (6 in the 9th year) of elementary education in public schools in the municipality of Bragança (PA), both in urban and rural areas, using questionnaire containing open questions related to academic training, and about the psychological suffering presented by some students and emphasizing the importance of mental health in the school context. The data were analyzed using the content analysis technique. Results indicated a high increase in students' psychological distress, identified through reports of self-harm, stress, anxiety and depression. Among the causes related to this suffering, the consequences of the COVID-19 pandemic were the predominant ones. Thus, the study highlighted the importance of planning and developing actions aimed at students' mental health. Such interventions must meet current demand and prevent other causes of psychological distress in the school context. Mental health must be discussed and promoted in this human training environment.